2002
DOI: 10.1046/j.1471-4159.2002.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of taurine transport at the blood–brain barrier by tumor necrosis factor‐α, taurine and hypertonicity

Abstract: Taurine is the abundant sulfur-containing b-amino acid in brain where it exerts a neuroprotective effect. Although it is known that the blood-brain barrier (BBB) mediates taurine transport, the regulation of taurine transport have not been clarified yet. A conditionally immortalized rat brain capillary endothelial cells (TR-BBB13), an in vitro model of the BBB, exhibited [3 H]taurine uptake, which was dependent on both Na + and Cl -, and inhibited by b-alanine. Taurine transporter (TAUT) mRNA was detected in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 40 publications
3
78
0
1
Order By: Relevance
“…Further, the BBB permeability clearances of several compounds estimated in TR-BBB cells appear quite similar to in vivo evaluations (Terasaki et al, 2003). TR-BBB cells have already been used to demonstrate that transporters such as taurine transporter (TauT), system A isoform (ATA2) are expressed in rat brain endothelium (Kang et al, 2002;Takanaga et al, 2002). Accordingly, we thought that TR-BBB cells are one of the best in vitro models of BBB, allowing for the investigation of the mechanism for transport of diverse compounds including various drugs.…”
Section: Discussionmentioning
confidence: 81%
“…Further, the BBB permeability clearances of several compounds estimated in TR-BBB cells appear quite similar to in vivo evaluations (Terasaki et al, 2003). TR-BBB cells have already been used to demonstrate that transporters such as taurine transporter (TauT), system A isoform (ATA2) are expressed in rat brain endothelium (Kang et al, 2002;Takanaga et al, 2002). Accordingly, we thought that TR-BBB cells are one of the best in vitro models of BBB, allowing for the investigation of the mechanism for transport of diverse compounds including various drugs.…”
Section: Discussionmentioning
confidence: 81%
“…Hyperosmotic culture medium (380 mOsm/kg) was prepared by adding 100 mM raffinose to normal culture medium. ]taurine uptake was performed through the previous report (Kang et al 2002) o C in the presence or absence of inhibitors. After appropriate time periods, uptake was terminated by removing the applied solution and cells were immersed in ice-cold ECF buffer.…”
Section: Cell Culturementioning
confidence: 99%
“…Cytokine is one of the factors modulating taurine uptake. TNF-α, an inflammatory cytokine, increases expression of TauT mRNA and intracellular taurine uptake (Kang et al, 2002;Mochizuki et al, 2002). Pre-treatment TNF-α increases taurine uptake more in TR-BBB13 than in rat astrocyte and human intestinal Caco-2 cells (Chang et al, 2001).…”
Section: Effect Of Calcium Channel Blockers On [ 3 H]taurine Uptakementioning
confidence: 99%
“…Although TAUT plays a dominant role in taurine transport (30), there are many unresolved issues. For instance, at the blood-brain barrier, there is a taurine-sensitive GABA transport that is hard to attribute to TAUT alone because it is also sensitive to betaine and nipecotic acid (31)(32)(33)(34)(35)(36)(37). Deletion of the TAUT gene in mice resulted in dramatic reductions (Ͼ80%) in tissue taurine levels in several tissues, including brain, kidney, plasma, and retina, as well as skeletal and heart muscle (30), but immunocytochemistry for taurine suggested that the taurine loss in hepatocytes was only 30% (38).…”
mentioning
confidence: 99%